Strong dependence of the hardness on fictive temperatures in far-from-equilibrium La57.5Ni12.5Al17.5Cu12.5 metallic glasses. (February 2018) - Wang, Yuting; Li, Pengfei; Wang, Li-Min
Abstract: The relation between the hardness of a non-equilibrium La57.5 Ni12.5 Al17.5 Cu12.5 glass and its fictive temperature T f is studied. The fictive temperatures are controlled by quenching rates and ageing times. The room-temperature hardness is measured for five pairs of glassy samples. Enhanced hardness is observed in the glasses with either increased ageing time or slower quenching rate. However, the hardness difference is not resolved for each pair of glasses of the same T f, showing a trivial memory effect. The results suggest the strong dependence of the hardness of glasses at far-from-equilibrium ( T ≪ T f ) on the fictive temperature, which allows for the evaluation of the hardness of the glasses. Highlights: The RT hardness of La57.5 Ni12.5 Al17.5 Cu12.5 glasses is strongly dependent on T f . The same fictive temperature of La57.5 Ni12.5 Al17.5 Cu12.5 glasses gives comparable hardness. The effect of thermal histories on the hardness in glass of far-from-equilibrium can be neglected.